Соціальні та кримінологічні проблеми використання електронного моніторингу в сучасних пенальних практиках - Ягунов, Дмитро Вікторович; Ягунов, Дмитрий Викторович; Jagunov, D. (My University, 2012)
The article is focused on research of electronic monitoring as a modern criminal measure. Despite its prevalence in modern penal practices, electronic monitoring is still characterized by novelty and unusual, especially in comparison with other, more traditional criminal law measures. The article examines the social, criminological, philosophical and ethical problems of broad implementation of electronic monitoring.
Ягунов Д. В. Соціальні та кримінологічні проблеми використання електронного моніторингу в сучасних пенальних практиках /Д. В. Ягунов // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 45. – С. 42-52.
Keywords: електронний моніторинг у кримінології; проблеми впровадження електронного моніторингу в кримінології; кримінологія; электронный мониторинг в криминологии; проблемы внедрения электронного мониторинга в криминологии; криминология; electronic monitoring in criminology; problems of introduction of electronic monitoring in criminology; criminology